Elections, legitimacy, and compliance in authoritarian regimes: evidence from the Arab world. Issue 8 (17th November 2021) - Williamson, Scott
ABSTRACT: Elections have been theorized to bolster compliance with authoritarian regimes by strengthening their coercive capacity, their ability to co-opt, and their legitimacy. While a growing body of research supports the coercive and co-optive functions of these elections, there is little systematic empirical evidence regarding elections' contributions to the legitimacy of autocrats. This article draws on survey data from eight authoritarian countries in the Arab world to show that respondents who perceive elections as freer and fairer are more likely to express acceptance of the regime's right to govern and less likely to participate in political protests, even when they disapprove of the regime's performance. In addition, a survey experiment implemented in Egypt and Morocco provides causal evidence that perceptions of electoral quality impact legitimacy beliefs and expressed willingness to protest. The findings indicate the importance of studying how authoritarian institutions influence popular beliefs about the legitimacy of autocratic rulers.